Predicting Multi-Scenario Land Use Changes and Soil Erosion in the Huaihe River Basin Based on Coupled PLUS-CSLE Model - GUO Weiling; XU Liuyang; JIA Jiang; GAO Chang; XIA Xiaolin; WANG Bangwen; ZHANG Jingyu; CHEN Lei; CHEN Yingjian (Shuitu Baochi Xuebao)
[Objective] Understanding the future temporal and spatial evolution of land use and soil erosion in the Huaihe River Basin is of significant importance for rational and coordinated use of land resources, formulating future soil and water conservation strategies, and promoting sustainable development strategies. [Methods] Based on the PLUS model and the Chinese Soil Loss Equation (CSLE), the land use patterns in the Huaihe River Basin under three scenarios—natural development, ecological protection, and rapid development—for the year 2030 were simulated, and the future soil erosion patterns in the basin under these three scenarios were predicted. [Results] (1) Under all three scenarios, there was a significant expansion of construction land, with a maximum expansion area of 187.80 km2, while other land types decreased to varying degrees. (2) The soil erosion intensity in the basin from 2015 to 2021 showed a downward-then-upward trend. The average soil erosion amounts were 221.96, 214.13 and 461.15 t/(km2·a), respectively. High-intensity erosion was mostly concentrated in the northeastern high-slope areas, which require special attention. (3) Geographic detectors indicate that slope, DEM, and soil properties were the main driving factors influencing the distribution of erosion in the basin. (4) In 2030, the soil erosion modulus under natural development, rapid development, and ecological protection scenarios were 295.48, 259.45 and 127.64 t/(km2·a), respectively. An ecological protection model with appropriate expansion of construction land can meet both ecological protection and economic development demands. [Conclusion] This study can provide insights for land use management and soil conservation measures within the basin and promote healthy development.